The Digital Life of Small Market Newspapers: Results from a multi-method study. Issue 7 (9th August 2019) - Ali, Christopher; Schmidt, Thomas R.; Radcliffe, Damian; Donald, Rosalind
Abstract : The established narrative around newspapers and their relationship with "digital" is predominantly gloomy. We've learned how newspapers missed the mark regarding digital distribution and how traditional working practices often led to slow adoption of digital tools. There's merit in this, yet it is not the entire story. We are missing insights into the smallest newspapers. This paper contributes to this conversation through an investigation into the digital life of small market newspapers. We conducted a multi-method study drawing on in-depth interviews with experts and practitioners, and a survey of journalists and editors at small market newspapers. Our findings point to considerable variety of experience. It is crucial not to discount these experiments, or fall victim to the assumption of digital backwardness and analog quaintness we often equate with small towns and smaller publications.